The Promoter of AtUSP Is Co-regulated by Phytohormones and Abiotic Stresses in Arabidopsis thaliana - Bhuria, Monika; Goel, Parul; Kumar, Sanjay; Singh, Anil K. (Frontiers in Plant Science, 2016)
Universal stress proteins (USPs) are known to be expressed in response to various abiotic stresses in a wide variety of organisms, such as bacteria, archaeabacteria, protists, algae, fungi, plants and animals. However, in plants, biological function of most of the USPs still remains obscure. In the present study, Arabidopsis USP gene (AtUSP) showed induction in response to abscisic acid (ABA) and various abiotic stresses viz. heat, dehydration, salt, osmotic and cold stresses. Additionally, in silico analysis of AtUSP promoter identified several cis-elements responsive to phytohormones and abiotic stresses such as ABRE, ERE, DRE and HSE etc. To functionally validate the AtUSP promoter, the 1115 bp region of promoter was characterized under phyrohormone and abiotic stress treatments. Deletion analysis of promoter was carried out by cloning the full length promoter (D0) and its three 5´ deletion derivatives, D1 (964 bp), D2 (660 bp) and D3 (503 bp) upstream of the β-glucuronidase (GUS) reporter gene, which were then stably transformed in Arabidopsis plants. The AtUSP promoter (D0) showed minimal activity under non-stress conditions which was enhanced in response to phytohormone treatments (ABA and ACC) and abiotic stresses such as dehydration, heat, cold, salt and osmotic stresses. The seedlings harboring D1 and D2 deletion fragments showed constitutive GUS expression even under control condition with increased activity almost under all the treatments. However, D3 seedlings exhibited complete loss of activity under control condition with induction under ACC treatment, dehydration, heat, oxidative, salt and osmotic stresses. Thus, present study clearly showed that AtUSP promoter is highly inducible by phytohormones and multiple abiotic stresses and it can be exploited as stress inducible promoter to generate multi-stress tolerant crops with minimal effects on their other important traits.